Review of the Cyanobacterial Genus Phormidesmis (Leptolyngbyaceae) with the Description of Apatinema gen. nov. - Denis Davydov; Anna Vilnet (Diversity, 2022)
Cyanobacteria are crucial components of biological soil crusts of polar landscapes and carry out many functions in subaerial environments. Simple untapered filamentous cyanobacteria are typically in the terrestrial biotopes. They appear to be a group with an abundance of cryptic taxa. We isolated 23 strains of cyanobacteria from the different habitats of the Arctic and temperate zone, from 10 locations in order to characterize their morphological and genotypic diversity. Phylogenetic analyses were conducted on the 16S and 16S–23S ITS rRNA gene regions using Bayesian inference and maximum likelihood. A morphological comparison of the isolated strains with similar known species, as well as its phylogenetic analyses, revealed that they belong to three species of the genus Phormidesmis (P. nigrescens, P. pristley, and P. communis)—and to the previously unknown genus of Leptolyngbyaceae. Using an integrative approach, we provide here a description of a new taxon Apatinema gen. nov.